(untitled) (Proceedings OPTIMAL, 2024)
This study evaluates the effectiveness of Tuina massage therapy in enhancing appetite among preschool children, utilizing a traditional approach to address modern health challenges. Conducted at TK Dharma Wanita Bethet, Kediri, Indonesia, between May and July 2024, the randomized controlled trial involved 30 children aged 3 to 5 years. Participants were divided into an intervention group, receiving Tuina massage three times per week for eight weeks, and a control group with no intervention. Appetite was assessed using a standardized questionnaire and food diaries maintained by parents, along with weight measurements taken at baseline, mid-intervention, and post-intervention. Results showed significant improvements in appetite scores in the intervention group compared to the control group, with a marked increase in appetite and modest weight gain observed over the study period (p < 0.01). Qualitative feedback indicated positive behavioral changes in the intervention group, such as increased interest in food and willingness to try new foods. The findings suggest that Tuina massage therapy may serve as a viable non-pharmacological option for managing reduced appetite in young children, providing a practical alternative for parents and healthcare professionals. Future studies with larger samples and diverse populations are recommended to validate these findings and explore the long-term effects of Tuina massage on pediatric appetite and nutrition